Atmosphere plasma treatment and Co heteroatoms doping on basal plane of colloidal 2D VSe2 nanosheets for enhanced hydrogen evolution. (16th September 2021) - Wang, Ruonan; Guo, Zenglong; Tan, Xueling; Zhang, Jifu; Yang, Lei; Wang, Wei; Cao, Lixin; Dong, Bohua
Abstract: Structural engineering of highly efficient electrocatalysts based on 2D transition metal dichalcogenides (TMDs) for hydrogen evolution reaction (HER) is of great significance for sustainable energy conversion processes. Herein, a novel basal-plane engineering of 2D colloidal VSe2 nanosheets has been developed for highly enhanced HER performance via a synergistic combination of atmosphere plasma (AP) treatment and Co basal-plane doping. Systematic experiments and theoretical calculations show that the AP treatment not only efficiently removes the organic ligands, but also introduces defects and cracks as more active sites on the basal plane; while the Co basal-plane doping and defects further optimize Gibbs free energy of hydrogen adsorbed on the Se sites. Such AP treated 5 % Co doped VSe2 electrocatalyst exhibits onset overpotential of only 160 mV, Tafel slope of 42 mV/decade and turnover frequency (TOF) of 6.4 S −1 at 260 mV, comparable to the most active TMDs electrocatalysts. This work provides fresh insights into the utilization of "clean surface", defects/cracks and heteroatom doping on basal plane of 2D nanosheets for catalytic application. Graphical abstract: A synergistic structure engineering of colloidal 2D VSe2 nanosheets via a combination of atmosphere plasma (AP) treatment and Co basal-plane doping is developed for enhanced hydrogen evolution. The AP treatment not only efficiently removes the organic ligand, but also introduces defects and cracks as more active sites on the basal plane; and the Co doping and defects further optimize Gibbs free energy, which contributes to improving the HER activity of VSe2 basal plane. Image 1 Highlights: Co atoms incorporated into VSe2 substrates were synthesized. Co doping and atmosphere plasma treatment activate the lazy inner plane of VSe2 . The optimum catalyst has excellent performance in electrocatalytic activity.